A new ichnospecies of Arthrophycus from the upper Cambrian-Lower Tremadocian of northwest Argentina: Implications for the arthrophycid lineage and potential in ichnostratigraphy - Mangano, Maria Gabriela (2005)
A new ichnospecies of Arthrophycus Hall 1852, A. minimus , is described from Upper Cambrian-Lower Tremadocian, shallow-marine strata of northwest Argentina. This new ichnospecies consists of small, long, regularly annulated hypichnial elements displaying subcircular to squarish cross-section and a ventral median groove. Side branches are occasionally present, but palmate, fan-like structures and scribbling patterns are absent. We adopt a relatively narrow diagnosis of Arthrophycus , suggesting that roughly annulated, cylindrical structures should not be included in this ichnogenus, unless other diagnostic features (i.e., squarish cross-section, median groove, zipper-like annulations) are also present. Arthrophycus is a common ichnotaxon in Ordovician-Silurian shallow-marine siliciclastic environments. Post-Paleozoic occurrences are removed from Arthrophycus . Arthrophycus has been proposed as a biostratigraphic index fossil in Ordovician-Silurian rocks. The presence of A. minimus in the Santa Rosita Formation of northwest Argentina indicates that Arthrophycus ranges at least from the Upper Cambrian-Lower Tremadocian with probable representatives in the Lower Cambrian and, therefore, its biostratigraphic utility is extended. Arthrophycus minimus represents the first Cambrian occurrence exhibiting not only fine, diagnostic morphologic features, but also the classical Arthrophycus behavioral pattern in dense monoichnospecific assemblages. The exploratory behavioral pattern displayed by A. minimus is simpler than that of the younger ichnospecies, particularly A. brogniartii, A. alleghaniensis, and A. lateralis . This is consistent with the basal position of A. minimus within the arthrophycid lineage.